2021
DOI: 10.1038/s41467-021-26312-w
|View full text |Cite
|
Sign up to set email alerts
|

Direct genome-wide identification of G-quadruplex structures by whole-genome resequencing

Abstract: We present a user-friendly and transferable genome-wide DNA G-quadruplex (G4) profiling method that identifies G4 structures from ordinary whole-genome resequencing data by seizing the slight fluctuation of sequencing quality. In the human genome, 736,689 G4 structures were identified, of which 45.9% of all predicted canonical G4-forming sequences were characterized. Over 89% of the detected canonical G4s were also identified by combining polymerase stop assays with next-generation sequencing. Testing using pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Similarly, rG4-seq, which is a variant of G4-seq, has enabled transcriptome-wide identification of RNA G-quadruplexes [ 57 ]. Recently, a novel method called G4-miner was used for genome-wide profiling of G-quadruplexes from standard whole-genome sequencing based on deviations in sequencing quality, with drop in sequencing quality at G-quadruplex structures [ 58 ]. Antibodies with high affinity for G-quadruplexes have been used for G4 ChIP-seq experiments to demonstrate genome-wide G-quadruplex structure formation in human cells [ 1 , 59 ].…”
Section: High-throughput Techniques To Identify Non-b Dna Structuresmentioning
confidence: 99%
“…Similarly, rG4-seq, which is a variant of G4-seq, has enabled transcriptome-wide identification of RNA G-quadruplexes [ 57 ]. Recently, a novel method called G4-miner was used for genome-wide profiling of G-quadruplexes from standard whole-genome sequencing based on deviations in sequencing quality, with drop in sequencing quality at G-quadruplex structures [ 58 ]. Antibodies with high affinity for G-quadruplexes have been used for G4 ChIP-seq experiments to demonstrate genome-wide G-quadruplex structure formation in human cells [ 1 , 59 ].…”
Section: High-throughput Techniques To Identify Non-b Dna Structuresmentioning
confidence: 99%
“…Recently, the G4‐Miner method was reported to be used to detect genomic G4s through a novel principle. [ 95 ] In the standard whole‐genome sequencing process of Illumina sequencing, the reaction buffer without K + cannot lead to the formation of stable G4s, but the existing unstable G4s can still cause abnormal fluctuations of the Phred quality scores. Through capturing the subtle changes in the sequencing quality of these sites with computational algorithm, the G4 structures can be directly predicted.…”
Section: High‐throughput Sequencing Methods For Detecting G4smentioning
confidence: 99%
“…Positive detection rate is low. [95] Detecting RNA G4s in cellular transcriptome rG4-seq Identifying the formation and stability of RNA G4s.…”
Section: G4-seqmentioning
confidence: 99%
“…This general output suggested that G4s might be involved in biological processes other than telomere maintenance. Consistently, bioinformatic analyses have highlighted the fact that putative G4-forming sequences are enriched at other genomic loci besides telomeres [ 5 , 6 ]. More recently, the results from several ChIP-Seq, CUT&Tag, and related sequencing studies in cells have supported this evidence as well [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 93%